Analisis Pengaruh Nilai Tukar (Kurs), Inflasi Dan Bi Rate Terhadap Indeks Harga Saham Sektor Property Dan Real Estate Di Bursa Efek Indonesia Periode 2010-2014 - Yuniatin, Indriana, Drs. M. Farid Wajdi, MM, Ph.d (2016)
The objective of this study is to determine the influence of currency rate, inflation rate and BI rate towards property and real estate stock price index in indonesian stock exchange during 2010-2014. The population of this study used stock price index in property and real estate sector. The sampling technique used in this study is census sampling or saturated sampling. The classical assumption that used in this study is normality-tested, , multiple collinear tested, and heteroskedastisitas. The analysis instrument used multiple regression analysis. 2 The hypothesis testing is done by F test, t-test and determination coefficient. The results shows that currency rate and BI rate has significant influence toward property and real estate stock price index. Beside, inflation rate hasn't influence toward property and real estate stock price index. Simultanously, the results shows that currency rate, inflation rate and BI rate has influence toward property and real estate stock price index.